Econometrics - Maddala, G.S. (New York: McGraw-Hill, 1977)
The landmark text, Introduction to Econometrics, now fully revised and updated in its new Fourth Edition, offers a fresh accessible, and well-written introduction to the subject of econometrics, which literally means "measurement in economics." . With a rigorous pedagogical framework, which sets it apart from comparable texts, the book also includes Web-based supplements such as an Instructor's Manual and data sets.
Includes index
Keywords: Econometrics